Case Report: Neonatal Varicella Acquired From Maternal Zoster - Lai, Jeffrey W.; Ford, Timothy; Cherian, Sarah; Campbell, Anita J.; Blyth, Christopher C. (Frontiers in Pediatrics, 2021)
The incidence of neonatal varicella has decreased dramatically since the introduction of the varicella vaccination. Although the varicella zoster virus is often associated with a mild infection, it may cause severe morbidity and mortality, particularly in the neonatal period and immunocompromised hosts. We report a case of neonatal varicella acquired from maternal zoster in a mother on biological immunosuppressive therapy. Following the diagnosis, the baby improved on antiviral therapy without any neurological sequelae. This case highlights the limited published data on neonatal varicella following varicella reactivation to inform practice. This includes the role of varicella zoster immunoglobulin in neonates exposed to maternal zoster, the degree of trans-placental immunity and optimum antiviral dosing and duration.